Library and Information Science Curriculum in a Changing Professional Landscape: The Case of Copyright Education in the United States - Kawooya, Dick; Ferullo, Donna; Lipinski, Tomas (Journal of Copyright in Education & Librarianship, 2019)
Despite the importance placed on copyright and intellectual property literacy by the American Library Association, as evidenced in the accreditation standards, issues pertaining to copyright education remain marginal in the library and information science (LIS) curriculum and research. Today, copyright intersects with every library and information service in any type of information institution, yet few librarians get copyright training as part of the formal LIS curriculum in library schools. Lack of copyright education leaves many librarians unable to properly identify and address copyright issues in the workplace. This paper offers a critical analysis of LIS programs over the past 10–12 years with a specific focus on trends in the teaching of copyright matters. Employing a qualitative methodology with a mixed-method approach, the authors analyzed the syllabi of courses dedicated to copyright and intellectual property offered at select LIS programs. The goal was to understand what the copyright courses cover, how they are taught, instructional sources and resources, and curriculum changes over time, where applicable. Findings show that the few LIS programs offering copyright courses have rigorous and dynamic copyright curriculum that constantly changes with the evolving copyright environment. The main takeaway and recommendation is that some kind of coordination is needed in the teaching of copyright and that LIS programs may need minimum standards for the core curriculum of copyright courses. The coordinating mechanism will ensure that periodic review of the core curriculum occurs and takes into account the rapid changes in the different library environments where library students work.